2010
DOI: 10.1073/pnas.0911465107
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-engineered vascular grafts transform into mature blood vessels via an inflammation-mediated process of vascular remodeling

Abstract: Biodegradable scaffolds seeded with bone marrow mononuclear cells (BMCs) are the earliest tissue-engineered vascular grafts (TEVGs) to be used clinically. These TEVGs transform into living blood vessels in vivo, with an endothelial cell (EC) lining invested by smooth muscle cells (SMCs); however, the process by which this occurs is unclear. To test if the seeded BMCs differentiate into the mature vascular cells of the neovessel, we implanted an immunodeficient mouse recipient with human BMC (hBMC)-seeded scaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
499
2
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 507 publications
(525 citation statements)
references
References 46 publications
13
499
2
3
Order By: Relevance
“…No significant differences were found between RGD and ADSC in terms of vascular remodeling, neovessel formation, inflammatory cell response, and cytokine secretion. This result is consistent with that reported by Roh et al 17 who showed, in a murine model of infrarenal IVC replacement, that the restorative patterns observed after implantation of a human bone marrow mononuclear cell-seeded polymer could be duplicated by replacing cells with MCP-1 grafting on the scaffold. We acknowledge, however, that in the absence of covalent binding, the PDO can dissolve from the surface of the polymer with the possibility that its soluble form may, at the opposite of our objective, act as an integrin blocker preventing cell adhesion.…”
Section: Figsupporting
confidence: 93%
See 3 more Smart Citations
“…No significant differences were found between RGD and ADSC in terms of vascular remodeling, neovessel formation, inflammatory cell response, and cytokine secretion. This result is consistent with that reported by Roh et al 17 who showed, in a murine model of infrarenal IVC replacement, that the restorative patterns observed after implantation of a human bone marrow mononuclear cell-seeded polymer could be duplicated by replacing cells with MCP-1 grafting on the scaffold. We acknowledge, however, that in the absence of covalent binding, the PDO can dissolve from the surface of the polymer with the possibility that its soluble form may, at the opposite of our objective, act as an integrin blocker preventing cell adhesion.…”
Section: Figsupporting
confidence: 93%
“…Another important finding from the previous work of our laboratory and others 12,[16][17][18] is that polymer-seeded cells are cleared over time, which leads to speculate that the grafted cells do not structurally integrate within the neovessel wall, but rather act as platforms releasing signalling molecules that may recruit host cells. This hypothesis provides a robust rationale for testing whether cells can, thus, be replaced by biomimetic compounds, which could duplicate their recruiting effects and promote self-healing.…”
Section: Figmentioning
confidence: 89%
See 2 more Smart Citations
“…This mechanism has, in part, been attributed to the critical role of VEGF in adult neovascularization, and prevention of neovessel regression [95][96][97]. Indeed, monocyte/macrophage infiltration associates with VEGF expression with the tissue-engineered constructs [98]. In addition to VEGF, recruited monocytes likely release multiple cytokines, which then orchestrate the proper vascular neovascularization of biodegradable implants.…”
Section: Decellularized Tissue-derived Matrices: the Biologic Countermentioning
confidence: 99%